Prediction and validation of buckling stress (σcrt) of the ceramic honeycomb cell walls under quasi-static compression. Issue 1 (31st December 2016) - Ramavath, Pandu; Biswas, Papiya; Ravi, Nakula; Johnson, Roy
Abstract: Alumina- and cordierite-based honeycombs with varying relative densities were extruded and sintered at the respective sintering temperatures. Solid samples are also prepared under identical conditions and flexural strength ( σ f ) was estimated by three-point bend measurements. Buckling stress of honeycombs are predicted based on σ f using standard equations and validated with quasi-static compression test along the channels of honeycombs with varying relative densities. The discrepancy observed on calculated and measured values is correlated with the pre-existing flaws indicating the criticality in close control of processing parameters.